RISK MANAGEMENT IN PROVIDING THE POPULATION OF THE RIVNE REGION WITH WATER IN THE CONTEXT OF THE EUROPEAN UNION WATER FRAMEWORK DIRECTIVE - Likho, Olena; Hakalo, Oksana; Zaleskуi Ivan (Вісник Національного університету водного господарства та природокористування. Серія «Сільськогосподарські науки», 2020)
The article considers some aspects of risk management in providing the population of the Rivne region with water in the context of the European Union Water Framework Directive. The article presented analysis of the main directives of the European Union in the field of implementation of water policy. Assessment results of risks level arising during providing the population with water from centralized and decentralized sources in the Rivne region are given in the article. Depending on the risk level, appropriate recommendations were worked out to optimize the water supply to the population of administrative districts of the region. Additional measures were proposed to resolve the problem of poor water quality in decentralized sources of water supply due to agricultural pollution, using the recommendations of the EU Water Policy Directives.